2023
DOI: 10.1680/jgeot.22.00329
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of MICP- and EICP-treated sands in simple shear conditions: a benchmarking with the critical state of untreated sand

Abstract: Microbial or enzyme-induced calcium carbonate precipitation (MICP/EICP) are relatively new ground improvement technique. In this study, the mechanical behaviour of biotreated (MICP/ EICP) and untreated sands were investigated in light of the critical state soil mechanics framework using a series of direct simple shear (DSS) tests. A wide range of CaCO3 content (CC), initial void ratio after consolidation (e0) and effective initial normal stress (σ′N0) was considered. The biotreated specimens showed improved sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…As illustrated in Fig. 2, the mechanical characteristics of MICP-treated soil undergo the following changes (Cui et al, 2021;Nafisi et al, 2019;Nafisi et al, 2021;Ahenkorah et al, 2023):…”
Section: Mechanical Features Of the Micp-treated Specimensmentioning
confidence: 99%
“…As illustrated in Fig. 2, the mechanical characteristics of MICP-treated soil undergo the following changes (Cui et al, 2021;Nafisi et al, 2019;Nafisi et al, 2021;Ahenkorah et al, 2023):…”
Section: Mechanical Features Of the Micp-treated Specimensmentioning
confidence: 99%
“…They found that, compared with the untreated sand, all EICP treatment methods significantly increase the erosion resistance of treated sand, and 1.0 M cementing solution is a more feasible option to achieve the optimal erosion resistance. Ahenkorah et al [ 22 ] conducted a direct simple shear (DSS) test and studied the mechanical properties of EICP-treated sand and untreated sand under critical conditions. Based on their study, compared with the treated samples under similar initial conditions, the EICP-treated samples have a higher shear strength, and the final state of the treated sand tends to have a lower percentage of voids than the untreated critical state sand.…”
Section: Introductionmentioning
confidence: 99%